Natural Walls of Anatolia: Formation and Development of Dis Kayaliklari as a Structural Landform (Sivas, Turkiye) - Uzun, Ali; Aylar, Faruk; Zeybek, Halil Ibrahim; Gurgoze, Serkan; Bahadir, Muhammet; Alemdag, Selcuk (Science Press, 2023)
The Dis Kayaliklari is one of the largest and most striking examples of crests in the world and is located between Eskidere and Bogazoren villages of the Imranli district of the Sivas province in Turkiye. The crests, which resemble castle walls when viewed from afar, have a real wall pattern due to the right-angled crack system of the bedrock when viewed closely. This study aims at investigating the geomorphological features of the Dis Kayaliklari and determining how the geological and geomorphological evolution of the Dis Kayaliklari took place and how the current formation mechanism continues. In the region, the mid-latitude continental climate prevails with cold humid winters and warm dry summers. The bedrock consists of Miocene bedded deposits of different resistance, folded by young tectonic movements. Dis Kayaliklari was formed by selective erosion of less resistant terrain around a pack of resistant rock on the steeper southern slope of an asymmetrical anticline. It has a length of 4750 m in the approximately northwest-southeast direction, a maximum height of 30 m, and a width varying between 5 and 8 m. In the present morphological appearance of the Dis Kayaliklari, it can be stated that the structure formed after the tectonic formation process was eroded under the control of the local climate and crest formation was realized. In the following process, the crest experienced a polycyclic process where different landforms were formed. There are smaller landforms such as karren, cave and rock window on Dis Kayaliklari, and macrofossil beds in some places. This highly attractive geomorphosite, unknown to wider public, should be investigated from various scientific aspects and should be brought to regional tourism by making the necessary infrastructure and promotion studies.
Uzun, Ali/0000-0003-3854-2780; Aleag, Selcuk/0000-0003-2893-3681;
Keywords: Structural Landform; Crest; Geosite; Dis Kayaliklari; Sivas